Missing Teeth and its Impact on oral function of the patients visiting Dental Colleges in Kathmandu. - Pokhrel,Prenit Kumar (2020)
SUMMARY: Aim: The aim of this study was to investigate how tooth loss affects the oral health related quality of life through an OHIP-14 questionnaire and additional questions among patients visiting the six different Dental Colleges in Kathmandu, Nepal. Materials and method: Data was obtained from a questionnaire based on the OHIP-14 form, additional questions and a clinical examination. The study was of a descriptive nature and consecutive patients visiting the Prosthodontics opd during the study period were enrolled until the desired sample size was met. Co investigators assigned in every dental colleges were responsible for the data collection. Assistant Research officer was responsible for coordination among the researchers. Data from completed forms were analysed with SPSS to investigate how tooth loss affects the oral health related quality of life (OHRQoL) Results Mean age was 47.6 years with a gender ratio of 48 % (n=119) male and 52 % (n=130) female. The mean number of missing teeth was 5, and the mean total OHIP score was 21.57 (SD 12.55). The most frequently impacted dimensions for the OHIP-14 were "Physical pain" (77 %) and "Psychological discomfort" (82.5 %). 96.8 % of the investigated population experiencing some form of impact on their OHRQoL. Conclusion: A large majority of the patients visiting different Dental Colleges experienced an impact on their OHRQoL due to the missing teeth. The number of missing teeth had an impact on OHRQoL, but the position of missing teeth had not. The OHIP score with the criteria used in this study was found to be higher in comparison to other international findings.